Tribulus terrestris Extracts: An Eco-Friendly Corrosion Inhibitor for Mild Steel in H2SO4 Medium - Chaudhary, Suchitra; Tak, Rakesh K. (Asian Journal of Chemistry, 2017)
The easily available plant Tribulus terrestris can be used as low-cost, eco-friendly corrosion inhibitor for mild steel in aggressive industrial environment. The inhibition efficiencies of different extracts (fruit, leaf and stem) in relation to the concentration of inhibitor and temperature were determined by mass loss method. Further electrochemical measurements (EIS and potentiodynamic polarization) were also done. Surface analysis was examined by scanning electron microscope. The adsorption process obeys Langmuir adsorption isotherm. All these analysis confirm that plant Tribulus terrestris has good properties to prevent the corrosion of mild steel in acidic medium.